Remote School Retention in Australia: Why do First Nations Students Disengage and Drop out? - Guenther, John; Oliver, Rhonda; Ober, Robyn; Holmes, Catherine (Australian and International Journal of Rural Education, 2024)
The Australian education system works well for most students. However, equitable access to secondary education is problematic for First Nations people living in remote communities. There is a strong emphasis on Year 12 completion as an indicator of successful engagement in remote First Nations education. This has been partly driven by Australian Government ‘Closing the Gap’ targets. Yet for remote students Year 12 Certificate attainment is trending down, from 113 in 2013 down to 82 in 2022. Nationally, the target to achieve 96% Year 12 or equivalent is not on track for achievement. This article explores what students, school staff and community members say leads to disengagement and dropout. It is based on research conducted in Western Australia and the Northern Territory during 2023 by a team of researchers from Batchelor Institute, Curtin University and University of Notre Dame. The research focused on remote and very remote Independent and Catholic schools. It engaged 229 in surveys and 136 in yarns or interviews. Most of the respondents were First Nations people.